Diagnostic Challenge and Management of Thymic Cavernous Hemangioma: A Case Report and Review of the Literature - Liu, Li; Zhang, Fangbiao; Wu, Zhijun; Tu, Shaosong; Li, Yan (Current Medical Imaging, 2023)
Objective: Thymic cavernous hemangioma (CH) as a benign lesion is extremely rare, and it is very difficult to distinguish it from other anterior mediastinal tumors on imaging. Case Presentation: We treated a 63-year-old woman with thymic CH that was incidentally found by chest computed tomography (CT). Contrast-enhanced chest CT described an anterior superior mediastinal mass, approximately 2.5cm in diameter, with centripetal enhancement and an increased range of enhancement in the delayed period. The tumor and thymus were completely resected by video-assisted thoracic surgery (VATS) to provide a definitive diagnosis and precise treatment. Postoperative pathology suggested that the tumor was a thymus cavernous hemangioma. Conclusion: We reported an extremely uncommon case of CH in the thymus and reviewed the previously published literature. CH can occur at any age and body tissue, and there is no significant difference between males and females. Most patients are asymptomatic, often found by chest CT. Enhanced chest CT suggested that an increased area of venous enhancement at a prolonged duration may be a feature of CH. Complete surgical resection is a safe and effective method for CH in the thymus.
Keywords: thymoma